PASSIVE AND IONTOPHORETIC PERMEATION OF CAPTOPRIL GEL: AN IN VITRO AND IN VIVO STUDY - Ashish Jain; Satish Nayak; Vandana Soni (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
The Objective of this work was to formulate and evaluate captopril gel to assess its suitability for transdermal delivery by passive and iontophoresis. A polymer gel was prepared using hydroxypropyl methyl cellulose and in vitro skin permeability was assessed in full thickness skin of rabbits and pigs. For in vivo studies New Zealand rabbits were used. In vitro passive permeation was carried out in Franz diffusion cell but for iontophoresis, diffusion cell was modified according to Glikfield design. Iontophoresis was performed at a current density of 0.5 mA/cm2via silver /silver chloride electrodes with passive controls but for in vivo study current density wasreduced to 0.1 mA/cm2. Blood samples were analyzed for drug content by HPLC. Results of the in vitro study indicated that iontophoresis considerably increased the permeation rate of captopril compared to passive controls in both the skin types (P<0.01). The plasma concentration of captopril was significantly higher (P<0.001) than that obtained in the passive controls. Results showed that the target permeation rates for captopril could be achieved with the aid of iontophoresis by increasing the area in an appreciable range.Key words: Captopril, iontophoresis, transdermal, Rabbit, Pigskin, in vitro, in vivo.